Wahyu sebagai Sumber Utama Kebenaran dalam Pendidikan Islam: Kajian Kritis terhadap Implementasinya di Era Modern - Aulia Herawati; Ulil Devia Ningrum; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research examines the role of revelation as the main source of truth in Islamic education and the challenges of its implementation in the modern era. Revelation, which consists of the Qur'an and Sunnah, provides fundamental guidance for the formation of moral values, ethics, and the main goal of Islamic education, namely to produce people who not only have intellectual intelligence, but also have noble character. However, along with the rapid development of science and technology, the application of revealed values ​​in education faces various challenges. Globalization, popular culture, and materialistic orientation in modern education often conflict with the principles of revelation, so new approaches that are relevant and adaptive are needed. Through critical studies, this research highlights the importance of integrating revealed values ​​with modern science as well as learning methods based on real practice, in order to strengthen Islamic identity amidst the challenges of the times. The results of this study show that Islamic education can remain relevant if it is able to combine the essence of revelation as a guide to truth with modern approaches, thereby forming a generation that is intelligent, has morals, and is able to face global challenges wisely.